CMA-Based design of a Novel structure for isolation enhancement and Radiation Pattern correction in MIMO antennas - Myeong-Jun Kang; Jaesun Park; Hyuk Heo; Longyue Qu; Kyung-Young Jung (Scientific Reports)
Abstract This paper presents novel MIMO microstrip patch antennas with dimensions of 40 × 80 × 1.6 mm³ incorporating a decoupling and pattern correction structure (DPCS) designed to mitigate mutual coupling and radiation pattern distortion, operating within 3.6–3.7 GHz. Using characteristic mode analysis (CMA), two key modes affecting coupling and pattern degradation are identified, with the DPCS strategically positioned to address these issues. Unlike other decoupling techniques, the DPCS requires no additional space or structural complexity, making it suitable for 5G MIMO systems. The proposed design achieves isolation up to 90 dB and enhances the realized gain of Port 2 by 3 dB at boresight in simulations. Fabricated antennas were measured, achieving peak isolation of 80 dB in an anechoic chamber. Additionally, measurements in a noisy environment confirmed the robustness of the design under realistic conditions. Measured radiation patterns verified the DPCS’s ability to correct the radiation pattern. Key MIMO performance metrics, including ECC (2 × 10⁻⁴), DG (≈ 10), CCL (< 0.2 bits/s/Hz), MEG (≈ -7 dB), and TARC (< -12 dB), affirmed the design’s superior performance. The proposed structure can be applied to a variety of applications such as high-density urban wireless networks and IoT systems, where maintaining high isolation and reliable communication are critical requirements.